Liberating methodological thinking in human sciences from grand theories - Kharlamov, Nikita A.; Baldursson, Einar Baldvin (Academic Quarter | Akademisk kvarter, 2016)
Many humanistic and social disciplines are naturally inclined to seek for human-, person-, self- centered focus, and develop a holistic theory of such. Such disciplines continually engage with philosophical, metaphysical and meta-theoretical perspectives. This engagement often leads to a singular focus on the necessity of a “grand unified theory” at the expense of any and all alternative perspectives. Properties of grand theories are discussed on the examples of Giddens and Bourdieu. It is argued that grand theories hamper a more productive focus on concrete phenomena. Robert Merton’s focus on “middle range” theories is revisited and its continuing relevance is highlighted. The level of abstraction characteristic of such theories, as well as the way they engage with the empirical social reality, are discussed. The article concludes by considering the paradoxical reductionism that can be observed in presumably the most anti-reductionist grand theories.